Pengaruh Profesionalisme Guru PAK Berdasarkan 1 Petrus 5:2-3 Terhadap Motivasi Belajar Siswa Kelas VII SMP Negeri 3 Tigapanah - Purba, Lamria; Keluanan, Yane Henderina; Silaban, Berton Bostang H. (Jurnal Christian Humaniora, 2022)
This type of research is Quantitative research that aims to give the influence of The Professionalism of Teachers of Christian Religious Education (PAK) on the learning motivation of students. The professionalism of PAK Teachers is one of the keys that must be owned by a PAK Teacher whose goal is to increase learning motivation for students and have a chance for students both to increase their learning interest even to changes in their character. On the other hand, a PAK Teacher must also be able to be an example as written in 1 Peter 5:2-3, that is, a teacher is like a Shepherd whose job is to guide, direct and even guide his sheep, as well as his duties with a Teachers of Christian Religious Education, must be able to be a shepherd and imitate the Lord Jesus as a Good Teacher and shepherd. Data collection techniques are carried out by spreading the questionnaire as a data collection. The results of the study showed Teacher Professionalism and Learning Motivation. Therefore, it is expected that there is a relationship between Teachers and Student's even Cooperation with parents as a support for Teachers to help increase student learning motivation in Christian Education Learning to improve their achievement in learning and provide very satisfactory results.